Clinical trials of N-acetylcysteine in psychiatry and neurology: A systematic review. (August 2015) - Deepmala; Slattery, John; Kumar, Nihit; Delhey, Leanna; Berk, Michael; Dean, Olivia; Spielholz, Charles; Frye, Richard
Highlights: NAC is a promising treatment for several psychiatric and neurological disorders. Further larger controlled clinical trials are needed. 2.0–2.4 g oral NAC total daily dosing was safe and well tolerated. Abstract: N-acetylcysteine (NAC) is recognized for its role in acetaminophen overdose and as a mucolytic. Over the past decade, there has been growing evidence for the use of NAC in treating psychiatric and neurological disorders, considering its role in attenuating pathophysiological processes associated with these disorders, including oxidative stress, apoptosis, mitochondrial dysfunction, neuroinflammation and glutamate and dopamine dysregulation. In this systematic review we find favorable evidence for the use of NAC in several psychiatric and neurological disorders, particularly autism, Alzheimer's disease, cocaine and cannabis addiction, bipolar disorder, depression, trichotillomania, nail biting, skin picking, obsessive-compulsive disorder, schizophrenia, drug-induced neuropathy and progressive myoclonic epilepsy. Disorders such as anxiety, attention deficit hyperactivity disorder and mild traumatic brain injury have preliminary evidence and require larger confirmatory studies while current evidence does not support the use of NAC in gambling, methamphetamine and nicotine addictions and amyotrophic lateral sclerosis. Overall, NAC treatment appears to be safe and tolerable. Further well designed, larger controlled trials are needed for specific psychiatric and neurological disorders where the evidence is favorable.